Increasing Mathematical Critical Thinking Skills Using Advocacy Learning with Mathematical Problem Solving - I Ibrahim; Imam Sujadi; Samsul Maarif; Sri Adi Widodo (Universitas Syiah Kuala, 2021)
The ability to think critically is one of the abilities students must possess. Students critical thinking skills have not been encouraging. There is a need for learning that can improve this ability, one of which is advocacy learning. The study aims to increase students critical thinking skills with open-ended mathematical problems in advocacy mathematics learning. This study is a nonequivalent control group design with a pre-test post-test control group. Sampling using cluster random sampling, randomization was carried out in classes at Junior High School 4 Bandung by taking two classes. Data analysis used Mann-Whitney, one-way ANOVA, and Tukey. The results showed that students treated with an advocacy approach by giving open-ended questions had better mathematical critical thinking skills than those who received conventional learning. Also, students with high prior knowledge had better critical thinking skills compared to the other two groups. This research implies that the advocacy can be used as an alternative to learning mathematics for students with high prior knowledge.